2021
DOI: 10.3389/fnins.2021.618098
|View full text |Cite
|
Sign up to set email alerts
|

The Novel KIF1A Missense Variant (R169T) Strongly Reduces Microtubule Stimulated ATPase Activity and Is Associated With NESCAV Syndrome

Abstract: KIF1A is a microtubule-dependent motor protein responsible for fast anterograde transport of synaptic vesicle precursors in neurons. Pathogenic variants in KIF1A have been associated with a wide spectrum of neurological disorders. Here, we report a patient presenting a severe neurodevelopmental disorder carrying a novel de novo missense variant p.Arg169Thr (R169T) in the KIF1A motor domain. The clinical features present in our patient match with those reported for NESCAV syndrome including severe developmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Similar to R167C, the ATPase analysis of K161A and K163A mutants also showed a significant decrease in the ATP hydrolysis rates and affinity for the microtubules (Additional file 1: Fig. S7H, I), consistent with the previous work that conversion of all the positively charged residues in loop8 to alanine (K161A/R167A/R169A/K183A) strongly affected MT-binding affinity [15,62,71]. We did not measure the ATPase activity of the R169A mutant because the motor showed very low expression levels even after 2 days in mammalian cells and failed to express in Sf9 cells despite several attempts.…”
Section: Kinesin-3 Motor Velocities Inversely Correlate To Their Micr...supporting
confidence: 88%
See 1 more Smart Citation
“…Similar to R167C, the ATPase analysis of K161A and K163A mutants also showed a significant decrease in the ATP hydrolysis rates and affinity for the microtubules (Additional file 1: Fig. S7H, I), consistent with the previous work that conversion of all the positively charged residues in loop8 to alanine (K161A/R167A/R169A/K183A) strongly affected MT-binding affinity [15,62,71]. We did not measure the ATPase activity of the R169A mutant because the motor showed very low expression levels even after 2 days in mammalian cells and failed to express in Sf9 cells despite several attempts.…”
Section: Kinesin-3 Motor Velocities Inversely Correlate To Their Micr...supporting
confidence: 88%
“…S7G), the mutant exhibited a significant decrease in the rate of ATP hydrolysis (~ 33%) and microtubule affinity (~ 1.5 times), compared to wild-type motors (Additional file 1 : Fig. S7H, I) [ 71 ]. The residue R167 establishes multiple stable interactions with MT in ATP and ADP states [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…KIF1A(P305L) reduces the microtubule association rate of the motor (27). KIF1A(R169T) disrupts the microtubule-dependent ATPase activity of the motor domain (28). KIF1A(R254W) reduces the velocity and run length of the motor protein (24) .…”
Section: Introductionmentioning
confidence: 99%
“…KIF1A(V8M) causes defects in force generation, while KIF1A(R254W), KIF1A(A255V), and KIF1A(R350G) have a shorter run length ( 27 , 31 , 32 ). The KIF1A(P305L) mutation strongly reduces the microtubule association rate of the motor, while KIF1A(R169T) disrupted the microtubule-dependent ATPase activity of the motor domain ( 33 , 34 ). On the other hand, we have suggested that KIF1A(V8M), KIF1A(A255V), and KIF1A(R350G) mutations (all of them are familial) result in a gain of function ( 25 ).…”
mentioning
confidence: 99%
“…KIF1A(P305L) mutation reduces microtubule association rate of the motor (32). KIF1A(R169T) disrupted the microtubule-dependent ATPase activity of the motor domain (33). KIF1A(R254W) mutation reduces the velocity and run length of the motor protein (27).…”
Section: Introductionmentioning
confidence: 99%